THE EFFECT OF EXTRACURRICULAR ACTIVITY TOWARD ENGLISH LEARNING ACHIEVEMENT OF NURSING STUDENTS - Juliana Juliana; Novi Afrianti (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2020)
This research is a descriptive correlative study. The purpose of this study was to determine the effect and relationship of English extracurricular activities (English Club) on the English learning achievement of nursing students. This research took place at the Academy of Nursing Kesdam Iskandar Muda Banda Aceh. The population in this study were all students of the Academy of Nursing Kesdam Iskandar Muda Banda Aceh. The samples are students of 2018/2019 who take part in English extracurricular activities as many as 50 students. Data collection methods in this study are the documentation and the questionnaire. Documentation is used to obtain data about the names and number of students who become research respondents. The questionnaire was used to find out students' opinions about English extracurricular activities. The data was analysed in term of percentage by using statistic descriptive SPSS 16.0 and Ms Excel 2013. The results of this study are the researchers found that the average value of students' perceptions reached 82.3% which means students strongly agree with the existence of English language extracurricular activities to support the improvement of their English learning achievement. The data is strengthened by the results of documentation of students' English grades. From the results of the analysis showed that English extracurricular activities proved to have an effect on students' English learning achievement.